2016
DOI: 10.1186/s12981-016-0092-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the sensitivity and specificity of First Response HIV-1-2 test kit with whole blood and serum samples: a cross-sectional study

Abstract: BackgroundHuman immunodeficiency virus (HIV) Rapid diagnostic Test (RDT) kits are the preferred assays for HIV testing in many countries. Prevention of Mother-to-Child Transmission, Know Your Status Campaigns, Blood-Safety, Voluntary Counseling and Testing are major strategies adapted to control transmission of the virus and the pivot of these interventions is either screening or diagnosing individuals through testing. There are reports of inconsistent sensitivity and specificity with whole blood and serum sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The use of Oraquick Advance Rapid HIV-1/2 antibody test is consistent with the confirmatory testing protocol for HIV in Ghana [30]. …”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…The use of Oraquick Advance Rapid HIV-1/2 antibody test is consistent with the confirmatory testing protocol for HIV in Ghana [30]. …”
Section: Methodsmentioning
confidence: 89%
“…Blood samples of hospital participants were further tested for HIV using INSTANTCHEK HIV-1 + 2 rapid diagnostic test kit by EY Laboratories and Oraquick Advance Rapid HIV-1/2 antibody test by OraSure Technologies, Inc. The use of Oraquick Advance Rapid HIV-1/2 antibody test is consistent with the confirmatory testing protocol for HIV in Ghana [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…used plasma samples that had been frozen, shipped and stored, whereas RDTs, while often validated for serum and plasma, are designed to be used with fresh specimens, typically capillary whole blood. While the limited data available do not indicate clear discordance with the testing results from previously frozen samples, as noted by the authors, “some studies have shown differences in sensitivity and specificity when using plasma/serum compared to capillary whole blood,” which could be postulated to have had an impact on the results seen .…”
Section: Discussionmentioning
confidence: 93%
“…For comparison, rapid diagnostic tests (RDTs) for HIV are reported to have 99% specificity, 32 , 33 but at least one RDT (First Response) had 100% specificity on whole blood but 82.86% specificity with serum specimen for HIV-1. 34 Comparing results with serum specimen, the HIV test would generate far more false positives than the Chagas RDT with serum that was used for estimating cost stated earlier.…”
Section: Discussionmentioning
confidence: 99%